(untitled) (Eurasian Scientific Herald, 2023)
Currently, the literature of the Turkic-speaking people and the history of the formation of this literature is undoubtedly related to the ancient Turkic inscriptions of Bilga Kagan, Kul Tigin, Tonyukuk. The article analyzes the roles of parallels and sounds of alliteration in the formation of parallels in the formation of poetry in the history of the Turkic language, presenting examples from ancient Turkic scripts and folklore works in manufacturing tourism